Genetic instability induced by low doses of x-rays in hamster cells - Seoane, Analia Isabel (2007)
Purpose: Genomic instability involves time delayed events and can be manifested as elevated rates of heritable changes in the progeny of irradiated cells. To study the induction of chromosomal instability by very low doses of radiation Chinese Hamster Ovary (CHO) cells were exposed to 10 - 50 milisieverts (mSv) (≈10 - 50 miligrays (mGy)) of x-rays. Materials and methods: Control and irradiated cell populations were assayed for chromosomal aberrations and assessed using a micronucleus test and anaphase-telophase analysis at the first cell division post-irradiation and at every four population doublings thereafter up to 16 population doublings post-irradiation. Results: Frequencies of micronuclei, anaphase-telophase alterations and chromosomal aberrations were increased when the cells were analysed immediately after x-ray exposure. Micronuclei and anaphase-telophase alterations showed significantly increased frequencies when they were analysed at 12 and 16 population doublings after exposure to 50 mSv. Chromosomal aberrations increased significantly at 12 and 16 population doublings after exposure to 10 mSv and 50 mSv. Conclusions: Our results are consistent with the presence of a phenomenon by which the initial DNA damage in the surviving cells is memorized. Micronuclei and achromatic lessions were the main cytogenetic damage observed in cells exposed to very low doses of x-rays, indicating that these low doses are able to induce genetic instability. © 2007 Informa UK Ltd.